Prospective randomized study to assess the efficacy of site and rate of atrial pacing on long-term progression of atrial fibrillation in sick sinus syndrome: Septal Pacing for Atrial Fibrillation Suppression Evaluation (SAFE) Study - Lau, Chu-Pak; Tachapong, Ngarmukos; Wang, Chun-Chieh; Wang, Jing-Feng; Abe, Haruhiko; Kong, Chi-Woon; Liew, Reginald; Shin, Dong-Gu; Padeletti, Luigi; Kim, You-Ho; Omar, Razali; Jirarojanakorn, Kreingkrai; et al. (Circulation (New York, N.Y.), 2013)
Atrial-based pacing is associated with lower risk of atrial fibrillation (AF) in sick sinus syndrome compared with ventricular pacing; nevertheless, the impact of site and rate of atrial pacing on progression of AF remains unclear. We evaluated whether long-term atrial pacing at the right atrial (RA) appendage versus the low RA septum with (ON) or without (OFF) a continuous atrial overdrive pacing algorithm can prevent the development of persistent AF. We randomized 385 patients with paroxysmal AF and sick sinus syndrome in whom a pacemaker was indicated to pacing at RA appendage ON (n=98), RA appendage OFF (n=99), RA septum ON (n=92), or RA septum OFF (n=96). The primary outcome was the occurrence of persistent AF (AF documented at least 7 days apart or need for cardioversion). Demographic data were homogeneous across both pacing site (RA appendage/RA septum) and atrial overdrive pacing (ON/OFF). After a mean follow-up of 3.1 years, persistent AF occurred in 99 patients (25.8%; annual rate of persistent AF, 8.3%). Alternative site pacing at the RA septum versus conventional RA appendage (hazard ratio=1.18; 95% confidence interval, 0.79-1.75; P=0.65) or continuous atrial overdrive pacing ON versus OFF (hazard ratio=1.17; 95% confidence interval, 0.79-1.74; P=0.69) did not prevent the development of persistent AF. In patients with paroxysmal AF and sick sinus syndrome requiring pacemaker implantation, an alternative atrial pacing site at the RA septum or continuous atrial overdrive pacing did not prevent the development of persistent AF. URL: http://www.clinicaltrials.gov. UNIQUE IDENTIFIER: NCT00419640.